Apolipoprotein E genotyping in women with recurrent pregnancy loss: An in silico and experimental hybrid study - Poursadegh Zonouzi, Ahmad; Farajzadeh, Davoud; Bargahi, Nasrin; Farajzadeh, Malak (Gene, 2014)
The role of apolipoprotein E gene polymorphisms in the pathogenesis of recurrent pregnancy loss remains controversial. Therefore, our objective was to investigate the association between recurrent pregnancy loss and apolipoprotein E gene polymorphisms among northwest Iranian women, and also to predict the impact of these nonsynonymous single nucleotide polymorphisms on structure and function of apolipoprotein E protein. The subjects of our current study consisted of 100 women that have had two or more consecutive idiopathic first trimester miscarriages, and one hundred healthy women from the same geographical areas were used as a control group. After DNA extraction, we used a polymerase chain reaction–restriction fragment length polymorphism to genotype of the apolipoprotein E gene. In addition, we predicted the possible effects of amino acid substitutions at codons 112 and/or 158 on the structure and function of apolipoprotein E protein using Polymorphism Phenotyping online software v2. Our results showed that the rate of apolipoprotein E ε4 carriers and the frequency of the ε4 allele in the case group were statistically and significantly higher than those in the control group (P<0.05). Therefore, our data support the association of the Apo ε4 allele with RPL; however, in silico analysis predicted that the amino acid substitution at residue 112 (Apo ε4 allele) is a benign mutation. Accordingly, further studies are required to elucidate the mechanism(s) underlying the link between RPL pathogenesis and the Apo ε4 allele. •The higher rate of Apo E ε4 carriers and higher frequency of ε4 allele is significant in case group.•The association of the Apo ε4 allele with RPL is presented.•It is shown that the amino acid substitution at residue 112(Apo ε4 allele) is a benign mutation.